Digital Blueprint for Excellence: PT. XYZ's Strategic IT Transformation in the Oil Industry - Wilfri Gultom, Donny; Sfenrianto, Sfenrianto (Ridwan Institute, 2024)
This study explores the essential role of Information System and Information Technology (IS/IT) strategic planning in optimizing organizational performance, focusing specifically on PT. XYZ, a leading national private company in the oil industry. PT. XYZ faces challenges such as the absence of a clearly documented IT development strategy, insufficient prioritization of IT system enhancements, and poor integration of existing applications, all contributing to operational inefficiencies. The primary aim of this research is to develop a comprehensive Information System/Technology Strategic Plan (ISSP) that aligns seamlessly with PT. XYZ's business strategies. Utilizing the Ward & Peppard methodology, this study conducts thorough analyses to maximize IT investments and ensure that IT strategies support the company's business objectives. The data collection and analysis methods include SWOT analysis, benchmarking, and synthesizing findings. The findings of this research provide PT. XYZ with a vital roadmap for IT development, prioritize IT initiatives in line with business goals, and enhance the integration of current and future applications, ultimately leading to improved operational efficiency.